2004
DOI: 10.1038/sj.eye.6701653
|View full text |Cite
|
Sign up to set email alerts
|

High-dose intravenous immunoglobulin in the treatment of toxic epidermal necrolysis: a study of ocular benefits

Abstract: Purpose To compare acute ocular complications of toxic epidermal necrolysis (TEN) following treatment with high-dose human intravenous immunoglobulin (IVIG) with a historical cohort not treated with IVIG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 30 publications
(30 reference statements)
1
37
2
Order By: Relevance
“…206 Finally, in a comparison of 10 treated patients with 18 historical controls, IVIG did not reduce the severity of the ocular complications of TEN. 207 It is difficult to reconcile the studies showing negative results with the large number of reports showing benefit, but one inference is that Fas-FasL is not the only pathway to apoptosis. 208 Other pathogenetic mechanisms, most notably perforin/ granzyme, must be involved.…”
Section: Tnf-a Inhibitorsmentioning
confidence: 96%
“…206 Finally, in a comparison of 10 treated patients with 18 historical controls, IVIG did not reduce the severity of the ocular complications of TEN. 207 It is difficult to reconcile the studies showing negative results with the large number of reports showing benefit, but one inference is that Fas-FasL is not the only pathway to apoptosis. 208 Other pathogenetic mechanisms, most notably perforin/ granzyme, must be involved.…”
Section: Tnf-a Inhibitorsmentioning
confidence: 96%
“…23 Though IVIg has been shown to block FasL from binding to Fas in vitro and initially showed promising results as a therapy for SJS/ TEN, 11,24-29 subsequent studies have shown limited clinical success. [30][31][32][33][34][35] There is some evidence that IVIg might be more effective for SJS/TEN as an adjunct to systemic corticosteroids. 36 Systemic corticosteroids, however, are a controversial topic in the acute management of SJS/TEN patients.…”
Section: Fas-faslmentioning
confidence: 99%
“…A small case series indicated that PS therapy in the acute phase prevented ocular complications, 35 but others indicated that systemic steroid or IVIG therapy did not limit ocular damage. 36,37 In this study, no systemic immunomodulatory treatments presented benefits on final visual outcome and chronic ocular complications. These results corroborate with the previous reports showing no benefits of systemic treatments on mortality.…”
Section: Discussionmentioning
confidence: 95%